Characterization of zeolite ore in the west and south of the coastal chain – Syria - Saflo, Nisreen Hosny; Habib, Moustafa; Rumie, Akel (Journal of natural sciences, life and applied sciences, 2023)
Nowadays, the rapid development has affected all technical, technological and other fields in terms of product diversity or multiple areas of use. Natural zeolite is considered one of the materials of great economic importance because it has a set of physio-chemical properties, which makes it an important material used in various industrial, agricultural and environmental fields.The zeolite-bearing deposits were described in the research area by studying samples taken from several sites. Where the petrographic study showed that the studied rocks represent the olivine basalt (the mother rock), which was determined based on the percentage of the dominant phenocryst crystal content of olivine, pyroxene and plagoclase, and we note that its thicknesses are variable from one site to another.The X.Ray.D diffraction measurement results showed that the metallic phases of the samples taken from the study area are divided into metallic groups: impulsive, sedimentary, and zeolitic, with confirmation of the presence of two distinct zeolitic phases in the study area from other regions in the diameter, namely (dachiardite and jamesonden). Three samples were selected and differential thermal analysis (DTA-TG) was conducted on them, showing that they have thermal stability within a wide range and that there is a slight endothermic effect at 900 ° C due to slight sintering of the zeolite structure.
Keywords: Zeolite; zeolitic phase; differential thermal analysis; The olivine basalt